A Deconstructive reading of Franz Kafka’s The Trial - Ghosh, Aditi (International Journal of Psychosocial Rehabilitation, 2024)
Kafka’s The Trial, an invisible and a unique piece of fiction, provides the readers with an ambience of uncertainty and sense of ambiguous and mysterious environment. Written in 1915 and posthumously published in 1925, Kafka’s The Trial narrates the story of Josef K, a banker, unexpectedly arrested and prosecuted by a remote, inaccessible and unspecified court system for a crime he says he was unaware of. Josef finds himself in an impossible, nightmarish and tormenting situation here charge which he is accused of and the justice is unknown and uncertain.The Trial it can be interpreted on many levels such as; as a brutal satire of the absurdity of unfair judicial systems, a frighteningly disturbing examination of the peculiarity of bureaucracy and a vivid demonstration of human weaknesses in face of authority such as the corporate control of the human lives exploiting people’s fear of losing jobs, the subjection of authority at the hands of accused being, thus destabilizing the hierarchies, decentering between the conscious and subconscious existence of K because the world revolving around himself is unpredictable and unclear. And this deconstructive reading has attempted to limit and differentiate what is “inside” or “outside” the work